SELF MANAGEMENT BEHAVIOUR PADA PASIEN YANG MENJALANI HEMODIALISA - Chrisyen Damanik; Runtiani . (ITKES Wiyata Husada Samarinda, 2018)
Self management behavior is a way of controlling oneself in order to achieve a desired target, the ability of patients with chronic kidney disease to regulate their lifestyle while experiencing illness conditions and undergoing changes in their lifestyle. The purpose of this study was identify self management behaviour in patients undergoing hemodialisa. This descriptive study was collectedfrom 62 respondent by using univariate analysis. The results of this study showed that average respondents had a maximum self-management behavior of 46.63. This study may be the information and results of the evaluation for nurses on self-management behaviors in patients with chronic kidney disease undergoing hemodialysis.